Agricultural education,the proliferation of training institutions to meet manpower needs for rural development in Malaysia. - Lassim, Mohd Shah (1985)
The main thrust of rural development efforts was on agricultural development and to develop agriculturae a core of trained personnel was needed which Malaysia lacked at the onset of independence in 1957. The paper based on a research project attempts to examine the proliferation of agricultural training institutions at the secondary level in Peninsular Malaysia and their roles in turning out skilled manpower as well as in educating farmers to accept new innovations and adopt appropriate technologies for increased productivity. Salient findings from this research are summarised as follows; - There are five Government Ministries involved in the propagation of vocational agricultural education and training and 92 training institutions have been established to date in Peninsular Malaysia alone. -Each agency formulated its own training policy quite independently in trying to meet individual aims and there was a lack of coordination among the various agencies resulting in duplication of some of the training programmes. -A common feature observed was that each agency developed training programmes for (1) the staff designed to upgrade skills and improve performance,and (2) the target group - the farmers,smallholders,settlers,fishermen,etc.to faciltate appropriate technology transfer. -There was an absence of standardisation among the various courses of training offered by various agencies involved.